The Living Is Easy - West, Dorothy, 1907-1998 (Book collections on Project MUSE., 2020)
"The Living Is Easy, Dorothy West's first novel and one of only a handful of novels published by women during the Harlem Renaissance, tells the story of Cleo Judson, daughter of Southern sharecroppers, who is determined to integrate into Boston's black elite. Married to the "Black Banana King" Bart Judson, Cleo maneuvers her three sisters and their children-but not their husbands-into living with her, attempting to recreate her original family in a Bostonian mansion. With a new foreword by Morgan Jerkins, The Living Is Easy is a classic of American literature."--